2018
DOI: 10.1002/hec.3800
|View full text |Cite
|
Sign up to set email alerts
|

The impact of waiting time on patient outcomes: Evidence from early intervention in psychosis services in England

Abstract: Recently, new emphasis was put on reducing waiting times in mental health services as there is an ongoing concern that longer waiting time for treatment leads to poorer health outcomes. However, little is known about delays within the mental health service system and its impact on patients. We explore the impact of waiting times on patient outcomes in the context of early intervention in psychosis (EIP) services in England from April 2012 to March 2015. We use the Mental Health Services Data Set and the routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 61 publications
4
88
0
1
Order By: Relevance
“…In addition, several studies document the value of physical examinations and initial primary care visits (Solberg, Maciosek, and Edwards, 2008;Zaman, 2018), which are the third most common reason for new patient appointments (Table 1). New patients also are more likely than established patients to need treatment for hearing loss and stress or mental health-related treatment-conditions for which timeliness of care is of utmost importance (Reichert & Jacobs, 2018). Veterans are a vulnerable population with a higher incidence of mental health issues and alcohol and drug abuse.…”
Section: Optimal Waits For New and Established Patientsmentioning
confidence: 99%
“…In addition, several studies document the value of physical examinations and initial primary care visits (Solberg, Maciosek, and Edwards, 2008;Zaman, 2018), which are the third most common reason for new patient appointments (Table 1). New patients also are more likely than established patients to need treatment for hearing loss and stress or mental health-related treatment-conditions for which timeliness of care is of utmost importance (Reichert & Jacobs, 2018). Veterans are a vulnerable population with a higher incidence of mental health issues and alcohol and drug abuse.…”
Section: Optimal Waits For New and Established Patientsmentioning
confidence: 99%
“…Therapists evaluate their level of knowledge regarding different psychological approaches, including Stanislav Grof's HMP (Grof, 2015) They demonstrate being open to a theoretical and experiential approach to HMP and its praxis, HB They indicate reasons for a theoretical and experiential approach to HMP and its praxis, HB Awareness of the limited diversity of psychological approaches presented in their academic background Knowledge of the main topics of HMP and their expansions relative to traditional approaches Attitude of commitment to the project's educational and experiential program Skill to organize their personal calendars to participate in project activities psychosis (Marshall & Rathbone, 2011;Reichert & Jacobs, 2018;Schmidt et al, 2015), a set of studies and early assistance for people with signs of psychological distress was implemented in 2001, taking as assumptions the observation that hospital admittance had not been shown to be the best option for those who present psychotic suffering prodromes and that proper and early management can interrupt the ongoing aggravating situation (Costa, 2017;Freitas & Costa, 2018 With that in mind, since its implementation, the program has been directed at people under severe psychological distress in their first-episode mental crisis of a psychotic type. Family participation has also been a criterion for inclusion in the program.…”
Section: Determinants and Change Objectives Methods Applicationsmentioning
confidence: 99%
“…Regarding the program development, it was observed that the model of early intervention in psychotic crises developed by GIPSI, albeit inspired by the English experience of early intervention in psychotic crisis (Marshall & Rathbone, 2011;Reichert & Jacobs, 2018;Schmidt et al, 2015), distances itself from this model while advancing some of its aspects, notably abandoning the "psychosis" diagnosis and evaluation based on prodromes of this pathology to look at the signs of disorganization and suffering that could indicate a mental health crisis (Freitas & Costa, 2018). Another peculiarity of the GIPSI Program is the inclusion of the family in the therapeutic care based on the understanding that suffering reverberates from the individual into their family environment.…”
Section: Determinants and Change Objectives Methods Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, timeliness is still the least studied and least understood dimensions of quality care. [2] Long waiting times (WT) may negatively affect health outcomes [3,4] and patient experience with clinical care, including perceived quality of care. [5] Canadian patients waiting for a consultation with a medical specialist for a new medical condition reported worry, stress, anxiety, deterioration of health and loss of work.…”
Section: Introductionmentioning
confidence: 99%